Development of amphibious mobile solar power generator with ultra water filtration system for disaster relief - Muhamad Zahin Mohd Ashhar,; Lim, Chin Haw (Penerbit Universiti Kebangsaan Malaysia, 2023)
During severe flood and natural disaster scenarios, electricity power becomes an essential and critical element to ensure the operation of medical services, equipment and communication systems as the power stations will most likely be shut down. Delivering power source and potable water to disaster areas becomes a major obstacle during severe flooding following the rise of water level causing road transportation becomes inaccessible. Therefore, an amphibian trailer equipped with a hybrid solar photovoltaic (PV) and an ultra-water filtration system is a good solution as it can be deployed or towed to the disaster areas by either a boat or a pickup truck. The amphibian trailer is equipped with a hybrid standalone solar PV system with battery storage and a generator set that can supply approximately 25 kWh of electric power per day. An ultra-water filtration system is also installed on the trailer, and it is powered by the hybrid solar PV system. Aluminium is used to construct the chassis of the trailer to ensure that the trailer is lightweight, strong, durable, and anti-corrosion. The wheeled trailer is integrated with a fiberglass floatable pontoon to allow it to operate on land and water. More importantly, the amphibious trailer can be relocated easily based on the situation and needs. This paper describes comprehensively the design and development process of the solar amphibious trailer.